Triangulating the Foundations of Kuyperian Spirituality - David Kristanto (Asosiasi Teolog Indonesia, 2021)
Spirituality is an under-developed topic on Abraham Kuyper, perhaps it is due to Kuyper’s strong emphasis on the public implications of Christian faith. But things are not supposed to remain that way, since Kuyper also has an equally strong emphasis on the importance of the private dimension of Christian faith. For more than 40 years, Kuyper had written a multivolume of meditations which amount to 2,200. In those meditations, his personality and spirituality are clearly reflected. This article argues that his meditations would be a suitable starting point to construct a Kuyperian spirituality alongside other Kuyperian themes such as his doctrine of regeneration (palingenesis) and his ecclesiology. The term “palingenesis” (from Greek word palingenesia) refers to both personal rebirth and the rebirth of all cosmos. This doctrine bridges the private and public implications of Christian faith, between spirituality and Christian actions in Kuyper’s theology. And while his distinction between the Church as institution and as organism is well-known, his emphasis on the role of the institutional Church as mother which nurtures the spirituality of the believers is lesser known. A deeper examination shows how his ecclesiology plays a central role in his spirituality.